Genomic Epidemiology and Global Population Structure of Exfoliative Toxin A-Producing Staphylococcus aureus Strains Associated With Staphylococcal Scalded Skin Syndrome - Azarian, Taj; Cella, Eleonora; Baines, Sarah L.; Shumaker, Margot J.; Samel, Carol; Jubair, Mohammad; Pegues, David A.; David, Michael Z. (Frontiers in Microbiology, 2021)
Staphylococci producing exfoliative toxins are the causative agents of staphylococcal scalded-skin syndrome (SSSS). Exfoliative toxin A (ETA) is encoded by eta, which is harbored on a temperate bacteriophage ΦETA. A recent increase in the incidence of SSSS in North America has been observed; yet it is largely unknown whether this is the result of host range expansion of ΦETA or migration and emergence of established lineages. Here we detail an outbreak investigation of SSSS in a neonatal intensive care unit, for which we applied whole-genome sequencing (WGS) and phylogenetic analysis of Staphylococcus aureus isolates collected from cases and screening of healthcare workers. We identified the causative strain as a methicillin susceptible S. aureus (MSSA) sequence type 582 (ST582) possessing ΦETA. To then elucidate the global distribution of ΦETA among staphylococci, we used a recently developed tool to query extant bacterial WGS data for biosamples containing eta, which yielded 436 genomes collected between 1994 – 2019 from 32 countries. Applying population genomic analysis, we resolved the global distribution of S. aureus with lysogenized ΦETA and assessed antibiotic resistance determinants as well as the diversity of ΦETA. The population is highly structured with 8 dominant sequence clusters (SCs) that generally aligned with S. aureus ST clonal complexes. The most prevalent STs included ST109 (24.3%), ST15 (13.1%), ST121 (10.1%), and ST582 (7.1%). Among strains with available data, there was an even distribution of isolates from carriage and disease. Only the SC containing ST121 had significantly more isolates collected from disease (69%, n=46) than carriage (31%, n=21). Further, we identified 10.6% (46/436) of strains as MRSA based on the presence of mecA and the SCCmec element. Assessment of ΦETA diversity based on nucleotide identity revealed 27 phylogroups, and prophage gene content further resolved 62 clusters. ΦETA was relatively stable within lineages, yet prophage variation is geographically structured. This suggests that the reported increase in incidence is associated with migration and expansion of existing lineages, not the movement of ΦETA to new genomic backgrounds. This revised global view reveals that ΦETA is diverse and is widely distributed on multiple genomic backgrounds whose distribution varies geographically.